PENGARUH AKUNTANSI PERTANGGUNGJAWABAN DAN KEPEMIMPINAN MANAJERIAL TERHADAP EFISIENSI BIAYA PADA PERUSAHAAN JASA RUMAH SAKIT DAN PUSKESMAS DI SURABAYA - Yuliana Numbung; Prayogi, Gusti Dian (Majalah Ekonomi, 2025)
The increasing operational costs in hospitals and community health centers in Surabaya including expenditures for medical supplies, equipment, and healthcare personnel salaries are often not balanced with the revenues generated from healthcare services. Additionally, disparities in the quality of healthcare services between hospitals and community health centers remain a significant issue, primarily due to challenges in managing high operational expenses, infrastructure inequalities, patient surges, and inefficient financial management. These conditions hinder efforts to maintain and improve service quality. This study aims to examine the influence of and community health centers in Surabaya. A descriptive and causal quantitative approach was employed. The population consisted of managers, unit heads, and accounting staff involved in financial and operational activities across various healthcare facilities. Purposive sampling was used to select respondents, and the Slovin formula was applied to determine a total of 192 participants. Data were collected through structured questionnaires. The findings indicate that both Responsibility Accounting and Managerial Leadership have a positive and significant impact on Cost Efficiency in hospitals and community health centers in Surabaya.